Interactions between species change the uptake of ammonium and nitrate in Abies faxoniana and Picea asperata. (28th December 2021) - Hu, Xuefeng; Li, Wanting; Liu, Qinghua; Yin, Chunying
Abstract: Plant nitrogen (N) uptake is affected by plant–plant interactions, but the mechanisms remain unknown. A 15 N-labeled technique was used in a pot experiment to analyze the uptake rate of ammonium (NH4 + ) and nitrate (NO3 − ) by Abies faxoniana Rehd. et Wils and Picea asperata Mast. in single-plant mode, intraspecific and interspecific interactions. The results indicated that the effects of plant–plant interactions on N uptake rate depended on plant species and N forms. Picea asperata had a higher N uptake rate of both N forms than A. faxoniana, and both species preferred NO3 − . Compared with single-plant mode, intraspecific interaction increased NH4 + uptake for A. faxoniana but reduced that for P. asperata, while it did not change NO3 − uptake for the two species. The interspecific interaction enhanced N uptake of both N forms for A. faxoniana but did not affect the P. asperata compared with single-plant mode. NH4 + and NO3 − uptake rates for the two species were regulated by root N concentration, root nitrate reductase activity, root vigor, soil pH and soil N availability under plant–plant interactions. Decreased NH4 + uptake rate for P. asperata under intraspecific interaction was induced by lower root N concentration and nitrate reductase activity. The positive effects of interspecific interaction on N uptake for A. faxoniana could be determined mainly by positive rhizosphere effects, such as high soil pH. From the perspective of root–soil interactions, our study provides insight into how plant–plant interactions affect N uptake, which can help to understand species coexistence and biodiversity maintenance in forest ecosystems.